Silver Recovery from Acidic Solutions by Formation of Nanoparticles and Submicroparticles of Ag on Microfiltration Membranes - González, Pilar; Recio, F. Javier; Ribera, Dario; González, Oswaldo; DaSilva, Pilar; Herrasti, Pilar; Avila-Rodriguez, Mario (IntechOpen, 2011)
None